Physical and electrical properties of thermal oxidized Sm2O3 gate oxide thin film on Si substrate: Influence of oxidation durations - Goh, K.H.; Haseeb, A.S. Md. Abdul; Wong, Y.H. (Elsevier, 2016)
Growth of 150 nm Sm2O3 films by sputtered pure samarium metal film on silicon substrates and followed by thermal oxidation process in oxygen ambient at 700 °C through various oxidation durations (5 min, 10 min, 15 min and 20 min) has been carried out. The crystallinity of Sm2O3 film and existence of interfacial layer have been evaluated by X-ray diffraction, Fourier transform infrared and Raman analysis. Crystallite size and microstrain of Sm2O3 were estimated by Williamson–Hall plot analysis. Calculated crystallite size of Sm2O3 from Scherrer equation has similar trend with the value from Williamson–Hall plot. The presence of interfacial layer is supported by composition line scan by energy dispersive X-ray spectroscopy analysis. The surface roughness and surface topography of Sm2O3 film were examined by atomic force microscopy analysis. The electrical characterization revealed that 15 min of oxidation durations with smoothest surface has highest breakdown voltage, lowest leakage current density and highest barrier height value.